2018
DOI: 10.3389/fpsyg.2018.00095
|View full text |Cite
|
Sign up to set email alerts
|

Father–Child Longitudinal Relationship: Parental Monitoring and Internet Gaming Disorder in Chinese Adolescents

Abstract: Although empirical studies have indicated that parents have an important role in preventing Internet gaming disorder in adolescents, longitudinal research on the parental predictors of Internet gaming disorder is lacking. We used a three-wave cross-lagged panel model to explore the reciprocal association between parental monitoring and Internet gaming disorder, and examined the different impacts of mother– and father–child relationships on this association. A sample of 1490 adolescents aged 10–15 years (M = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 55 publications
(98 reference statements)
8
78
0
6
Order By: Relevance
“…We tested both positive (i.e., social support and positive interpersonal relationships) and negative (i.e., perceived parental psychological control and negative interpersonal events/experiences) interpersonal correlates of adolescent IGD and the results support our hypotheses. Consistent with previous studies [11,18], we found that perceived support obtained from parents and peers and perceived positive interpersonal relationships with parents and peers were significantly associated with IGD. It is known that perceived social support and positive relationships with parents/peers are important resources of resilience and positive coping, as previous studies have shown that such resources could reduce stress, facilitate adaptive coping, and prevent maladaptive behaviors among adolescents [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We tested both positive (i.e., social support and positive interpersonal relationships) and negative (i.e., perceived parental psychological control and negative interpersonal events/experiences) interpersonal correlates of adolescent IGD and the results support our hypotheses. Consistent with previous studies [11,18], we found that perceived support obtained from parents and peers and perceived positive interpersonal relationships with parents and peers were significantly associated with IGD. It is known that perceived social support and positive relationships with parents/peers are important resources of resilience and positive coping, as previous studies have shown that such resources could reduce stress, facilitate adaptive coping, and prevent maladaptive behaviors among adolescents [12].…”
Section: Discussionsupporting
confidence: 91%
“…Family and parents play central roles in adolescents' socialization, behavioral development, and health [15]. Increasing studies have identified various family-related risk factors of IGD, including parental modelling of online gaming (e.g., parental gaming behavior [16] and parental attitudes [11]), poor parent-child relationship (e.g., perceived parental inconsistency [17], parental rejection [8], poor parental supervision [11,18]), poor family environment (e.g., poor family functioning [11], perceived family disharmony [6], and poor family cohesion [19]). Traditional Chinese culture and some Asian cultures emphasize parental psychological control (i.e., parental control that intrudes on the psychological and emotional development of the child) [20]; the attribute is a stressor and an interpersonal risk factor of adolescents' mental distress and behavioral problems [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, mother-child attachment and self-esteem do not appear to mediate the association between parental marital conflict and increases in IGD features. These findings are consistent with the results of previous longitudinal research [13,44]. The findings could be interpreted in terms of the Bowlby's attachment theory, in which affective bonds between infant and caregiver, who is typically a mother, form during infancy.…”
Section: Discussionsupporting
confidence: 91%
“…Fatherchild relationship (but not mother-child relationship) played an important role in the relationship between parental monitoring and IGD in Chinese adolescents. A previous study examined the different impacts of mother-and father-child relationships on IGD [44]. Unlike infancy, fatherhood influenced adolescent mental health more than motherhood.…”
Section: Discussionmentioning
confidence: 99%
“…However, mother-child attachment and self-esteem do not appear to mediate the association between parental marital conflict and increases in IGD features. These findings are consistent with results of previous longitudinal research 40,41 . The findings could be interpreted in terms of Bowlby's attachment theory, in which affective bonds between infant and caregiver, who is typically a mother, form during infancy.…”
Section: Discussionsupporting
confidence: 93%